Congenital Syngnathia in Bangladesh: A Very Rare Case Report - Rahaman, Muhammad Mizanur; Kabir, Mohammad Iqbal; Rabby, Md Atiqul Islam; Rahman, Md Masudur; Uddin, Md Nasir; Rashid, Md Harun Ur; Rahman, Tarin; Rab, Md Abdur; Chowdhury, Golam Mohiuddin; Morol, AKM Sobhan; et al. (Medicine Today, 2015)
Syngnathia is a rare anomaly involving fusion between the maxilla and mandible. The fusion may be due to soft tissue adhesion between the two or true bony fusion between maxilla and mandible. This condition ranges from only soft tissue fusion between gums known as synechia to bony union known as synostosis with different grades of fusion. It was first reported in 1936, with only 41 cases reported till 2009. In this case a 11 years old girl reported to the maxillofacial department of Dhaka Dental College Hospital, with the complaint of inability to open the mouth and as a diagnosed case of alveolar bone fusion of mandible with palatal alveolar bone in the left side & bone fusion of alveolar process of mandibular angle region with maxilla in the right side. She was also bone fusion of the coronoid process with zygoma in the right side. Immediate after birth she had a history of synechia (Bilateral) & it was correct by making stoma by maxillofacial surgeon. The patient was subjected to a surgical procedure, after successful operation she enabled to open her mouth up to 35 mm. Medicine Today 2014 Vol.26(2): 114-117